Infiltration Characteristics Of Tropical Soils At USM Engineering Campus - Goh, Kim Meng (Universiti Sains Malaysia, 2006)
This study was at University Sains Malaysia Engineering Campus. This study include infiltration test of predetermined geo-grid locations. 50 location were selected for infiltration test. Geostatistical analysis were performed on the infiltration test data to examine the spatial variability of infiltration over the study area. Semivariogram parameters (rang, nugget and sill), were used to characterize the spatial variability of infiltration sales. For the Geostatical analysis GS+ software was uses. Spatial variability map of infiltration rates were prepared using SURFER software. The campus area was classified in two areas namely, disturbed & undisturbed area.